نموذج التدريس للتربية الاسلامية لدى المدرسة الاعدادية الاهلية في اندونيسيا ( البحث عن المدرسة الاعدادية روضة العلوم الاسلامية غوينجان ترانجكيل فاطي ) - Muzakki, Abdullah (TAWASUT, 2024)
Education is an important issue in one’s life. It’s has many advantages for people. In modern era education is more done in the schools than in homes. So the education which is taught in the schools today is the modern education. School is the main place where people take his formally education. It has the medium that give them the skills, techniques, information and knowledge to know. To be like that school must have some strategy and device in accordance. Strategic management and planning provide the proper ground for defining the roadmap of any educational complex to develop success in schools. In general the most important strategic management success factor in any educational complex is its human resources which make it possible to achieve a successful school. Added Strategic learning that focused on students as active self- determined individuals who process information and construct knowledge